Factors Influencing Sanitation Management in Slums on The Riverbank of Kotalama Urban Village - Diana Putri Wijayanti; Fauzul Rizal Sutikno; Surjono Surjono (CV. AFDIFAL MAJU BERKAH, 2023)
One of the largest slum areas is located in Malang's Kotalama sub-district, which is distinguished by a considerable area that has undergone development along the riverbanks. The main challenge encountered in the area which has undergone development along the riverbanks, pertains to the insufficient management of sanitation. The aim of this research is to identify the sanitation conditions in the slum settlements within Kotalama sub-district and analyze the driving and inhibiting factors influencing sanitation management efforts in these slum settlements. The research method used is qualitative research. The results of the study concluded that 1) sanitation conditions in Kotalama District were in the